Allometric versus traditional body-shape indices and risk of colorectal cancer: a Mendelian randomization analysis - Rontogianni, Marina; Bouras, Emmanouil; Aglago, Elom Kouassivi; Freisling, Heinz; Murphy, Neil; Cotterchio, Michelle; Hampe, Jochen; Lindblom, Annika; Pai, Rish K.; Pharoah, Paul D. P.; Phipps, Amanda I.; van Duijnhoven, Franzel J. B.; et al. (International journal of obesity, 2024)
Background: Traditional body-shape indices such as Waist Circumference (WC), Hip Circumference (HC), and Waist-to-Hip Ratio (WHR) are associated with colorectal cancer (CRC) risk, but are correlated with Body Mass Index (BMI), and adjustment for BMI introduces a strong correlation with height. Thus, new allometric indices have been developed, namely A Body Shape Index (ABSI), Hip Index (HI), and Waist-to-Hip Index (WHI), which are uncorrelated with weight and height; these have also been associated with CRC risk in observational studies, but information from Mendelian randomization (MR) studies is missing. Methods: We used two-sample MR to examine potential causal cancer site- and sex-specific associations of the genetically-predicted allometric body-shape indices with CRC risk, and compared them with BMI-adjusted traditional body-shape indices, and BMI. Data were obtained from UK Biobank and the GIANT consortium, and from GECCO, CORECT and CCFR consortia. Results: WHI was positively associated with CRC in men (OR per SD: 1.20, 95% CI: 1.03–1.39) and in women (1.15, 1.06–1.24), and similarly for colon and rectal cancer. ABSI was positively associated with colon and rectal cancer in men (1.27, 1.03–1.57; and 1.40, 1.10–1.77, respectively), and with colon cancer in women (1.20, 1.07–1.35). There was little evidence for association between HI and colon or rectal cancer. The BMI-adjusted WHR and HC showed similar associations to WHI and HI, whereas WC showed similar associations to ABSI only in women. Conclusions: This large MR study provides strong evidence for a potential causal positive association of the allometric indices ABSI and WHI with CRC in both sexes, thus establishing the association between abdominal fat and CRC without the limitations of the traditional waist size indices and independently of BMI. Among the BMI-adjusted traditional indices, WHR and HC provided equivalent associations with WHI and HI, while differences were observed between WC and ABSI.
Gesehen am 01.07.2024